Professional footballers have a limited understanding of the precompetition medical assessment and the possible outcomes including disqualification: a cross-sectional survey - Mark L Fulcher; Thomas J Chin; Arier C L Lee (BMJ Open Sport & Exercise Medicine)
Objectives To determine professional footballers’ level of understanding of the purpose of the precompetition medical assessment (PCMA) and to evaluate their knowledge of potential outcomes following a PCMA, including disqualification.Methods Professional footballers from the Australasian A-League and Westfield W-League were asked to complete a 25-question survey. The relationship between dichotomised outcomes and explanatory variables was analysed with multivariate logistic regression; p<0.05 was considered statistically significant.Results A total of 212 players participated (response rate=48.8%). Most respondents selected ‘To detect medical conditions that may affect performance’ and ‘To detect current injuries’ (n=137, 64.6%; n=130, 61.3%) as the purpose of a PCMA. Approximately one-third (n=74, 38.1%) were neutral or believed that a normal PCMA prevented cardiac arrest. Receiving more PCMAs (p<0.0003) and receiving an explanation during their PCMA (p=0.0175) led to greater awareness of the assessment’s limitations. Most participants did not know the definitions of syncope (n=181, 93.3%) or Marfan syndrome (n=183, 94.3%). Fifty players (28.1%) did not know that disqualification was a possible outcome of a PCMA, and younger players were less aware of this possible outcome (p=0.0216).Conclusion Professional footballers appear to have a limited understanding of the purpose of a PCMA, emphasising the musculoskeletal system and performance. They also appear unfamiliar with the components of the PCMA and medical terms. Finally, many are unaware that disqualification can result from an abnormal PCMA. Player health knowledge must be improved; the informed consent process appears an ideal time to provide this education.